2014
DOI: 10.1111/jgs.12709
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Variation in Pain Following Inpatient Palliative Care Consultations

Abstract: Studies have documented high levels of pain in hospitalized individuals at the end of life, with minorities reporting higher levels of pain than whites. In response, inpatient palliative care (IPC) teams have grown rapidly to improve care of seriously ill individuals. Although research indicates that IPC teams effectively reduce and maintain control of pain, racial and ethnic differences in pain following IPC consultation remain unclear. This study investigated racial and ethnic pain differences after an IPC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…There are a few other studies which have looked at change in symptoms within 24 h of palliative care consultation and shown improvement [8,14,18], but most studies have looked at improvement over a longer time frame, ranging between 3 days after consultation and the time of discharge [9][10][11][12][13]15,16]. This finding is particularly relevant for a few reasons.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…There are a few other studies which have looked at change in symptoms within 24 h of palliative care consultation and shown improvement [8,14,18], but most studies have looked at improvement over a longer time frame, ranging between 3 days after consultation and the time of discharge [9][10][11][12][13]15,16]. This finding is particularly relevant for a few reasons.…”
Section: Discussionmentioning
confidence: 78%
“…The results may not be generalizable to institutions where similar palliative care services are not available or where the patient population is different. Our cohort was racially homogenous and there is some evidence that pain control after palliative care consultation may differ by race [18]. We did not have a control group and therefore cannot draw conclusions regarding a causal relationship between palliative care consultation and improvement in symptom burden.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Lu et al 13 found the opposite to be true when studying children; NHWs displayed more pain sensitivity as compared with AAs. In addition, Laguna et al 14 and Ford et al 15 found no significant difference between ethnicities in baseline pain ratings prior to palliative care consultation in populations of patients with dementia or in the hospital. Furthermore, no difference was found in prevalence of headache/migraine among ethnicities in a previous study.…”
Section: Discussionmentioning
confidence: 95%